Two sides of the same coin: a complex presentation of autosomal dominant tubulointerstitial kidney diseases: a literature review and case reports - Margareta Fistrek Prlic; Sanda Huljev Frkovic; Sanda Huljev Frkovic; Bodo Beck; Ivana Tonkovic Durisevic; Stela Bulimbasic; Stela Bulimbasic; Marijana Coric; Marijana Coric; Lovro Lamot; Lovro Lamot; Ema Ivandic; et al. (Frontiers in Pediatrics, 2023)
IntroductionGenetic kidney diseases are underdiagnosed; namely, from 7% to 40% of patients suffering from chronic kidney disease (CKD) can carry a pathogenic variant, depending on population characteristics. Hereditary tubulointerstitial kidney diseases, including autosomal dominant tubulointerstitial kidney diseases (ADTKD), are even more challenging to diagnose. ADTKD is a rare form of genetic kidney disease resulting from pathogenic variants in the MUC1, UMOD, HNF1B, REN, SEC61A1, and DNAJB11 genes. There is no typical clinical or histopathological sign of ADTKD, it is characterized by progressive CKD, an autosomal dominant inheritance pattern, and tubular atrophy with interstitial fibrosis on kidney biopsy. There is no significant proteinuria, and the urinary sediment is bland. The patients usually do not have severe arterial hypertension. There can be a history of early gout, especially when compared to the UMOD gene variants. Children can have enuresis due to a loss of renal concentration. On ultrasound, the kidneys can appear normal or small in size. Renal cysts are not pathognomonic for any of the named diseases. End-stage renal disease (ESRD) develops at the average age of 45, but this can be very variable. Family history that suggests autosomal dominant inheritance and CKD fulfilling the aforementioned characteristics of tubulointerstitial kidney disease should raise suspicion of ADTKD. In the setting of a negative family history for CKD, clinical suspicion should be raised based on clinical characteristics, including early onset of hyperuricemia or gout and compatible histology on the kidney biopsy. Contrary to the aforementioned characteristics of ADTKD, in the case of HNF1B-related disease, there is a more complex clinical presentation with extrarenal manifestations of the disease (diabetes mellitus, hypomagnesemia, neurologic and psychiatric disturbances, etc.). The diagnosis of ADTKD is based on a positive family history and a detection of the pathogenic variant in one of the genes in an affected individual.AimThe aim of our study is to present two case reports of ADTKD with different characteristics (slowly progressive CKD vs. complex clinical presentation with an extrarenal manifestation of the disease) with a literature review.MethodsA 34-year-old patient with CKD and a positive family history of CKD in whom kidney biopsy showed nonspecific chronic changes, with only genetic analysis confirming the diagnosis of MUC1-related ADTKD. Our second case is of a 17-year-old patient with an unremarkable family history who was initially referred to genetic counseling due to cognitive and motor impairment with long-lasting epilepsy. Extensive workup revealed increased serum creatinine levels with no proteinuria and bland urinary sediment, along with hypomagnesemia. His genetic analysis revealed 17q12 deletion syndrome, causing the loss of one copy of the HNF1B gene, the AATF, and the LHX1 gene.ConclusionAutosomal dominant tubulointerstitial kidney diseases are challenging to diagnose due to a lack of typical clinical or histopathological signs as well as an uncharacteristic and versatile clinical presentation. Increased clinical awareness is crucial for the detection of these diseases.